Characteristics of Verbs with Destructive Meaning in Russian and Serbian Languages - Maja R. Krstich (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The relevance of the study is proved by the fact that the category of destructiveness and the means of its implementation have not received any detailed analysis in linguistics so far. The object of the study is comprised of the verbs with destructive meaning in the Russian and Serbian languages, since these units form the core of the lexical- semantic field of destructiveness. The purpose of the article is to give a comprehensive (multi-level) description of verbs with the semantics of destructiveness, to highlight their specificity in the languages compared. It has been established that in the Russian and Serbian languages, verbs with the semantics of destructiveness fall into four groups: verbs with the meaning of damage; disappearance; destruction, decomposition; harm. It is shown that destructive verbs are characterized by a specific paradigmatic defect caused by semantic barriers. The comparison of the paradigms of verbs with a destructive meaning in the Russian and Serbian languages revealed that in both languages these units are characterized by two-term paradigms, in the Russian language there are verbs with a five-term paradigm, in the Serbian language such units are not represented. It has been revealed that the filling of zero paradigmatic positions in verbs with a five-term paradigm occurs through analytical constructions; verbs with a two-term paradigm do not need to be replaced, since they denote destructive actions, which do not require the forms of the 1 st or 2 nd person.